2023
DOI: 10.7717/peerj.15106
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with length of hospital stay and medical expenses in pulmonary abscess patients: retrospective study

Abstract: Background Pulmonary abscess carries a high mortality and requires long-term managements. A better understanding of the risk factors associated with the prolonged hospital stay and high medical expenses in these patients can improve the management strategy in individual patient and optimize the overall healthcare resources. Methods We performed a retrospective study and reviewed the medical records on consecutive patients hospitalized at the Department of Respiratory Medicine of the General Hospital of North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Additionally, Prevotella has been enriched in other respiratory infections, including pulmonary empyema, lung abscess, inhalation pneumonia, chronic otitis, and sinusitis. 34 , 35 , 36 Prevotella has also been identified as one of the most prevalent bacterial populations in the oropharynx of HIV-positive patients. During COVID-19, the prevalence of Prevotella has been found to be higher in infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Prevotella has been enriched in other respiratory infections, including pulmonary empyema, lung abscess, inhalation pneumonia, chronic otitis, and sinusitis. 34 , 35 , 36 Prevotella has also been identified as one of the most prevalent bacterial populations in the oropharynx of HIV-positive patients. During COVID-19, the prevalence of Prevotella has been found to be higher in infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Use of hydrocortisone and polymicrobial ventilator-associated pneumonia were identified as risk factors for developing LA. Not surprisingly, another study also reported that patients with LA had longer hospital stays compared to patients without LA [14]. In a study of 222 patients with LA, which was coauthored by us, the most common predisposing factors for LA were chronic obstructive pulmonary disease (35%), use of sedatives (29%), and alcohol misuse (22%) [15 ▪▪ ].…”
Section: Epidemiologymentioning
confidence: 91%